Mechanical properties of a balsa wood veneer structural sandwich core material. (30th December 2020) - Wu, Chao; Vahedi, Niloufar; Vassilopoulos, Anastasios P.; Keller, Thomas
Highlights: Orthotropy on the material scale and system scale influenced the mechanical behavior. The configuration of the veneer layers strongly affected the specimen responses. The adhesive between the veneer layers did not affect the mechanical behavior. Abstract: Balsa wood is an appropriate core material for structural sandwich applications due to its high strength- and stiffness-to-weight ratios. However, the mechanical properties vary considerably owing to the inherent scattering of natural wood materials. One approach to reduce this scatter and tailor the mechanical properties according to specific application needs is to recompose the natural material into a veneered material consisting of veneer layers of different grain orientations, which are adhesively bonded together. The mechanical properties of such a veneered balsa wood, composed of alternating 0°/90° grain orientations, were investigated at ambient temperature according to corresponding standards. The properties were significantly influenced by the orthotropy on the material scale within one veneer layer and on the system scale within the assembled veneer layers. Standardized experimental set-ups and specimen geometries may produce artifacts such as buckling or strain hardening which deviate from the material behavior in real structures. The thin adhesive between the veneer layers did not negatively affect the mechanical behavior since failure occurred within the veneer layers and not in the interfaces.